Tunisia : 2017 Article IV Consultation and Second Review Under the Extended Fund Facility, and Request for Waivers of Nonobservance of Performance Criteria, and Rephasing of Access. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Tunisia's economic growth almost doubled to 1.9 percent in 2017, as confidence strengthened on the back of improved security and the unity government's early progress with policy and reform implementation. Investment and exports remained sluggish, however. Growth is expected to reach 2.4 percent in 2018, helped by a good agricultural season and a pickup in manufacturing and tourism. The unemployment rate remains high at 15 percent. Trade data for early 2018 show an improvement in export performance, while import growth is slowing. This favorable trend is expected to continue throughout the remainder of the year, supported by a more favorable real exchange rate.